Exploring the Nutraceutical Potential of Dried Pepper Capsicum annuum L. on Market from Altino in Abruzzo Region - Della Valle, A.; Dimmito, M. P.; Zengin, G.; Pieretti, S.; Mollica, A.; Locatelli, M.; Cichelli, A.; Novellino, E.; Ak, G.; Yerlikaya, S.; Baloglu, M. C.; Altunoglu, Y. C.; et al. (MDPI AG, 2020)
Sweet pepper is a typical type of Capsicum annuum from Abruzzo region, recognized as a traditional and local product, traditionally cultivated in the town of Altino (Abruzzo region, Italy). The aim of this study is to compare the sweet type of peppers from Altino with the hot pepper cultivated in the same area, in order to delineate their different phytochemical and biological profiles in vitro and in vivo. In this study, we elucidated their phytochemical composition, fatty acids composition and phenolic/flavonoid contents in extracts. Then antioxidant and enzyme inhibition assays were performed to evaluate their biological properties, together with in vitro cell assay and in vivo anti-inflammatory activity. Microwave (1000 mg/mL) extract of hot pepper showed the best inhibition value on in vitro cell growth assay; in fact, the number of survived cells was about 20% and 40% for microwave and Soxhlet extracts, respectively. In vivo anti-inflammatory assay revealed good activity for both species, which, when associated with in vitro cell inhibition results, could explain the protective effect on human prostatic hyperplasia.
Keywords: nutraceuticals; Capsicum annuum; chemical composition; Therapeutics. Pharmacology; RM1-950; functional ingredients; Capsicum annuum; nutraceuticals; chemical composition; functional ingredients Asphodeline-Aanatolica; prostate-cancer; inflammation; capsaicin; profile; Article; 3. Good health